(untitled) (Bulletin KNOB, 2006)
Een tekenboekje uit 1812 en 19de-eeuwse huisplattegronden The ’drawing book’ from 1812 was compiled by the building contractor and architect Johannes van Straaten (1781-1856). He exerted himself for the education of young building engineers. The booklet provided training in contract drawing, which concerned the very precise drawings belonging to building specifications. As examples Van Straaten designed a few modern houses. Since not much was built in those days, these examples are important. The booklet contains two kinds of examples, the first being a group of four civilian houses, the second three large houses for the rich. Only the former group of four is dealt with here, forming a coherent series of simple to more luxurious houses. The façades are modern, the floor plans still show the old-fashioned layout with three successive rooms. However, they are provided with modern elements such as doublé doors (porte-brisé) between rooms and alcove niches for beds. The most important aspect was the change in the form of staircases. The staircases were now placed against the side wall, with the corridors running between the staircase and the rooms. The front and back rooms were equally wide and connected en suite. This new form of staircase proved to be suitable for complete houses as well as for flats and left its mark on 19th century housing.